Zakat Untuk Pemberdayaan Ekonomi Mustahik Di BAZNAS Kabupaten Kuantan Singingi Riau - Fitrianto, Fitrianto (UIN Sunan Kudus, 2018)
Zakat in Islam is a treasure worship and zakat is the obligation of Muslims who already have wealth to meet the value of nisab and haul which must be distributed to Asnaf directly or through zakat institution. National Amil Zakat Agency (BAZNAS) Kuantan Singingi is an official government zakat institution that has been in operation in 2007 and has raised a large amount of zakat funds. In 2015 zakat fund raising has increased significantly to reach the amount of Rp. 2,162,988,234. The accumulated zakat funds are distributed by BAZNAS Kuantan Singingi in various program models such as consumptive zakat program, health services in the form of medical aid, educational scholarships, and habitable housing development for asnaf, and productive zakat programs such as asnaf skills training and venture capital in various businesses. These programs are proclaimed to improve the mustahik welfare in Kuantan Singingi district of Riau.